Texting bans and fatal accidents on roadways : do they work? - Abouk, Rahi (2013)
Reports that evidence shows that bans enforced as secondary offences have no appreciable effect on accidents. Adds that any reduction in accidents following texting bans is short-lived, with accidents returning to former levels within a few months.